PERAN LOTRE SEBAGAI SARANA AMAL BAGI ANAK-ANAK PANTI ASUHAN PROTESTAN DI SEMARANG TAHUN 1887-1935 - Anggita Anggita (Prabayaksa: Journal of History Education, 2026)
This study explores the financial instability faced by the Protestant Orphanage in Semarang and the need for adaptive funding strategies, which makes the use of lotteries an important subject of inquiry. It aims to analyze why lotteries were adopted as a philanthropic strategy to overcome financial uncertainty between 1887 and 1935, as well as how this practice contributed to the orphanage’s sustainability and development. Using historical method, comprising topic selection, heuristics, verification, interpretation, and historiography, this research draws on primary sources such as De Locomotief and Algemeen Handelsblad voor Nederlandsch-Indië, complemented by newspapers including Java-Post and Het Koloniaal Weekblad, as well as official reports and books. Founded in 1769, the orphanage became a de facto government institution following the Java War. Although the government assumed responsibility in 1845, its financial support remained unstable due to shifting colonial budget priorities and limited fiscal commitment, leading to recurring shortages. The tension between state responsibility, religious authority, and internal management reached its peak in 1874, repositioning the orphanage as a subsidized private institution. However, traditional fundraising efforts and repeated appeals for increased subsidies failed to resolve its financial constraints. In response, the orphanage turned to lotteries as a pragmatic solution, reflecting a negotiation between colonial administrative practices and religious values. Despite moral objections from religious figures who viewed lotteries as a form of gambling, the government approved a large-scale lottery in 1898 to fund a new building. The initiative not only covered construction costs but also generated significant profit. This study demonstrates how lotteries became a critical mechanism for the orphanage’s survival and expansion, revealing the complex interplay between philanthropy, morality, and colonial governance.